2012
DOI: 10.1021/es301144q
|View full text |Cite
|
Sign up to set email alerts
|

How Many Mountains Can We Mine? Assessing the Regional Degradation of Central Appalachian Rivers by Surface Coal Mining

Abstract: Surface coal mining is the dominant form of land cover change in Central Appalachia, yet the extent to which surface coal mine runoff is polluting regional rivers is currently unknown. We mapped surface mining from 1976 to 2005 for a 19,581 km(2) area of southern West Virginia and linked these maps with water quality and biological data for 223 streams. The extent of surface mining within catchments is highly correlated with the ionic strength and sulfate concentrations of receiving streams. Generalized additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
161
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 210 publications
(179 citation statements)
references
References 21 publications
10
161
1
Order By: Relevance
“…These results are consistent with earlier observations that the salinity, sulfate, and Se concentrations in MTM streams are linearly proportional to the extent of surface mining in the watershed. 14,15 A mass-balance calculation, using the Sr and 87 Sr/ 86 Sr in a mixing model, provides a sensitive evaluation of the fraction of the tributaries contributing to each of the downstream sampling points along the Mud River (Figure 1). We estimate that the tributaries provide between 5% and 33% of the dissolved constituents in the mainstem at different sampling locations along its flow (Figure 1 and Table S3, Supporting Information).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with earlier observations that the salinity, sulfate, and Se concentrations in MTM streams are linearly proportional to the extent of surface mining in the watershed. 14,15 A mass-balance calculation, using the Sr and 87 Sr/ 86 Sr in a mixing model, provides a sensitive evaluation of the fraction of the tributaries contributing to each of the downstream sampling points along the Mud River (Figure 1). We estimate that the tributaries provide between 5% and 33% of the dissolved constituents in the mainstem at different sampling locations along its flow (Figure 1 and Table S3, Supporting Information).…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…15 A survey quantifying the extent of surface mining in southern West Virginia revealed that the extent of surface mining disturbance within a catchment is highly correlated with the ionic strength and sulfate concentrations of the receiving streams. 14 The majority of coal production from surface mines in the southern Appalachian of West Virginia is derived from the Middle Pennsylvanian Kanawha and Allegheny formations (Figures S1, S2, Supporting Information). The Kanawha Formation is composed mostly of sandstone, gray and black shale (Carbolith), siltstone, and hosts several coal seams, including the high quality Coalburg and Stockton coals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These concerns are easily addressed via modification of TITAN's output (i.e., IndVal maxima are output as part of every TITAN object) or post hoc simulation (see appendix 1 in Bernhardt et al 2012) with minor effect on TITAN's core analysis. TITAN is relatively unique in its goal of deconstructing community responses into taxon-specific change as a complement to ecotoxicology, species distribution modeling, and community analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We developed more realistic simulations using negative binomial distributions with overdispersion in R (version 2.15.1; R Development Core Team, Vienna, Austria; Appendix S1; available online from: http://dx.doi.org/10.1899/12-142.1.s1). We set mean abundance across observations to range from 2 to 10 individuals, which approximates the range of empirical values we have observed in our analyses of various survey data sets (e.g., King and Baker 2010, Bernhardt et al 2012. We set mean abundance to be a function of the response models suggested by fig.…”
Section: Unrealistic and Inappropriate Simulated Datamentioning
confidence: 99%
See 1 more Smart Citation